Confusing Blood Group Antibodies in Obstetrics: Focus on the Risk of Hemolytic Disease of the Fetus and Newborn - Blackall, Douglas P.; Tomlinson, Mark W. (American Journal of Perinatology, 2025)
During routine prenatal antibody screening, maternal reactivity is sometimes detected for which the clinical significance is unclear. As a result, the strategy for monitoring these antibodies during pregnancy, to mitigate the risk of hemolytic disease of the fetus and newborn (HDFN), may be uncertain. This review focuses on four such immune responses in obstetrics: anti-G, anti-M, warm reactive autoantibodies, and apparent nonspecific immune responses that cannot be further classified. The relationship of these antibodies to HDFN is a primary focus. Related concerns, including maternal and neonatal transfusion considerations and candidacy for Rh immune globulin, are also addressed.
Keywords: alloimmunization; anti-G; anti-M; blood group antibodies; hemolytic disease of the fetus and newborn; pregnancy; warm reactive autoantibodies